2006
DOI: 10.1901/jaba.2006.144-05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Varying Levels of Treatment Integrity on Child Compliance During Treatment With a Three‐step Prompting Procedure

Abstract: The effects of three levels of treatment integrity (100%, 50%, and 0%) on child compliance were evaluated in the context of the implementation of a three-step prompting procedure. Two typically developing preschool children participated in the study. After baseline data on compliance to one of three common demands were collected, a therapist implemented the threestep prompting procedure at three different integrity levels. One integrity level was associated with each demand. The effects of the integrity levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 3 publications
3
81
0
Order By: Relevance
“…Researchers have systematically manipulated levels of integrity and demonstrated functional relationships between integrity and treatment outcomes (e.g., Carroll et al 2013;DiGennaro Reed et al 2011;St. Peter Pipkin et al 2010;Wilder et al 2006). Otherwise, effective treatments that are implemented with low treatment integrity may lose their efficacy (Carroll et al 2013;DiGennaro et al 2011;Fryling et al 2012;St.…”
mentioning
confidence: 99%
“…Researchers have systematically manipulated levels of integrity and demonstrated functional relationships between integrity and treatment outcomes (e.g., Carroll et al 2013;DiGennaro Reed et al 2011;St. Peter Pipkin et al 2010;Wilder et al 2006). Otherwise, effective treatments that are implemented with low treatment integrity may lose their efficacy (Carroll et al 2013;DiGennaro et al 2011;Fryling et al 2012;St.…”
mentioning
confidence: 99%
“…Research has shown that high treatment integrity is associated with positive therapeutic outcomes (Fiske 2008;Noell et al 2002;Wilder et al 2006). Unfortunately, and despite receiving pre-service training, many practitioners do not maintain acceptable treatment integrity over time Noell et al 2000).…”
mentioning
confidence: 99%
“…The intervention consisted of the job coach's systematic use of brief, least-to-most prompting with contingent praise. The three-step prompting process (Wilder, Atwell, & Wine, 2006) was referred to as SWAT Support, an acronym for "say, wait and watch, act out, and touch to guide." SWAT Support consisted of the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…Even when FSS is implemented with modest fidelity, improvements in student outcomes have been achieved (Walker et al, in press). However, a growing literature supports the importance of intervention fidelity for long-term program effectiveness (e.g., Arkoosh et al, 2007;Barber, Crits-Christoph, & Luborsky, 1996;Duchnowski, Kutash, Sheffield, & Vaughn, 2006;Joyce & Shower, 2002;Luborsky, McLellan, Woody, O Brien, & Auerbach, 1985;Sterling-Turner, Watson, & Moore, 2002;Wilder, Atwell, & Wine, 2006). When a systematic intervention program is faded (in the case of FSS from coach to teacher), the student is likely to continue to behave well for a period of time even if the intervention is not implemented with fidelity.…”
Section: Effectiveness Research For First Step To Successmentioning
confidence: 99%